Theatre of Marvels - Dillsworth, Lianne (Hutchinson, 2022)
Crowds gather at Crillick's Variety Theatre, where curiosity is satisfied with displays of intrigue and fear. They're here for the star of the show -- the Great Amazonia warrior. They needn't know this warrior is in fact Zillah, a mixed-race actress from the East End fooling them each night with her thrilling performance. But something is amiss, and when Crillick's new act goes missing Zillah feels compelled to investigate, knowing the fates that can befall women in Victorian London. From the bustle of the West India Docks to the coffee houses of Fleet Street to the parlours of Mayfair, Zillah's journey for answers will find her caught between both sides of her own identity, and between two men -- her wealthy white admirer, and an African merchant appalled by her act. Will Zillah be forced to confront the price of her own performance? And in risking everything can she also save herself?